2009
DOI: 10.1021/ef800865a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pH and SDBS on the Stability and Thermal Conductivity of Nanofluids

Abstract: Aiming at the dispersion of nanoparticles which are regarded as the guide of heat transfer enhancement, we investigated the heat transfer enhancement of two water-based nanofluids, namely, water-Al 2 O 3 and water-Cu mixtures. The absorbency, ζ potential, and thermal conductivity of the nanofluids were measured under different pH values and different sodium dodecylbenzene sulfonate (SDBS) dispersant concentrations. The results showed that the stability and thermal conductivity of nanofluids were highly depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(65 citation statements)
references
References 15 publications
1
60
0
Order By: Relevance
“…Fedele et al [157] showed that the ultrasonication method of nanoparticles dispersion was more effective than ball milling when they prepared DI-water-based nanofluids of CuO, TiO2 and SWCNHs. The addition of surfactant (dispersant or surface modifier) or pH modification was also shown to be effective [157,180]. However, there have been reports that surfactant and pH sometimes lead to an unnecessary increase in viscosity of nanofluids when not properly modified [82,211].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fedele et al [157] showed that the ultrasonication method of nanoparticles dispersion was more effective than ball milling when they prepared DI-water-based nanofluids of CuO, TiO2 and SWCNHs. The addition of surfactant (dispersant or surface modifier) or pH modification was also shown to be effective [157,180]. However, there have been reports that surfactant and pH sometimes lead to an unnecessary increase in viscosity of nanofluids when not properly modified [82,211].…”
Section: Discussionmentioning
confidence: 99%
“…This is because pH modification has a direct link with the electrostatic condition of the interface between the suspended particles and the fluid medium. In another pH influence investigation, Wang et al [180] systematically prepared optimised Al2O3-water and Cu-water nanofluids by the two-step method using the zeta potential, nanoparticle size and absorbency of the nanofluids as stability indicators. They varied the pH and surfactant concentration (in this case, sodium dodecylbenzene sulfonate (SDS)) to synthesise a stable nanofluid as indicated by the measured values of zeta potential and absorbency.…”
Section: Nanofluid Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Other similar works have shown that modifying the pH of nanofluid suspension further beyond the IEP have led to the formulation of stable nanofluids. [20][21][22][23] All the above cited literatures are unanimous on the fact that at IEP (point of zero charge on nanoparticles) the nanoparticles will aggregate due to insufficient electrostatic force to overcome the effectiveness of VDW forces of attraction. If the pH changes further away from the IEP, the ionic charge state of the particle surface increases which produces sufficient electrostatic repulsive force that overcomes the VDW forces of attraction.…”
Section: Introductionmentioning
confidence: 99%
“…The stability is due to a large negative zeta potential of Au nanoparticles in water. The influence of pH and sodium dodecylbenzene sulfonate (SDBS) on the stability of two water-based nanofluids was studied [24], and zeta potential analysis was an important technique to evaluate the stability. Zhu et al [25] measured the zeta potential of Al 2 O 3 -H 2 O nanofluids under different pH values and different SDBS concentration.…”
Section: Zeta Potential Analysismentioning
confidence: 99%